Fibromyalgia, Sjogren's & depression: linked?. Issue 7 (2nd October 2020) - Loganathan, Muruga; Ladani, Amit; Lippmann, Steven
ABSTRACT: Health care has become increasingly fragmented, partly due to advancing medical technology. Patients are often managed by various specialty teams when presenting with symptoms that could be manifestations of different diseases. Approximately one third of them are referred to specialists, at over half for outpatient appointments. Fatigue, pain, depression, dry mouth, headaches, and arthralgia are common complaints and frequently require referral to specialist physicians. Differential diagnoses include fibromyalgia (FM), Sjogren's syndrome (SS), and depression. Evaluations involve various sub-specialist especially physicians like those practicing pain management, rheumatology, and psychiatry. Thresholds for referring vary. Patients sometime feel lost in a 'medical maze'. Disagreement is frequent between specialties regarding management. Each discipline has its own diagnostic and treatment protocols and there is little consensus about shared decision-making. Communication between doctors could improve continuity. There are many differences and similarities in the pathophysiology, symptomatology, diagnosis, and treatment of fibromyalgia, Sjogren's syndrome, and depression. Understanding the associations between fibromyalgia, Sjogren's syndrome and depression should improve clinical outcome via a common holistic approach.